Control simultáneo y gestión administrativa en la Municipalidad Provincial de Maynas 2025 - Fasanando Tello, Juan Daniel (2025)
The purpose of this research was to determine how simultaneous control is related to administrative management in the Provincial Municipality of Maynas 2025. The study was a basic, non-experimental cross-sectional design. The sample consisted of a total population of 60 workers. In the results, of a total of 60 respondents in Simultaneous control and administrative management in the Provincial Municipality of Maynas 2025, in the variable Simultaneous control, we can see that 15.0% responded that it is bad and 46.7% stated that it is good; in the variable administrative management, 11.7% gave a response that it is bad, and 50.0% stated that it is good. In addition, the chi-square test showed a significance value of 0.000<0.05, indicating that there is a significant relationship between simultaneous control and administrative management in the Provincial Municipality of Maynas 2025.